Asymmetric construction of densely functionalized three-dimensional aza-tetracyclic scaffolds for drug discovery. Issue 98 (18th November 2022) - Umedera, Kohei; Morita, Taiki; Nakamura, Hiroyuki
Abstract : Asymmetric synthesis of 3D tetracyclic scaffold has been achieved. Three substituents (R 1, R 2, R 3 ) were introduced in two different 3D patterns, providing opportunity to explore vast chemical space and thus discovery of novel bioactive compounds. Abstract : Asymmetric construction of densely functionalized three-dimensional aza-tetracyclic scaffolds were achieved by intramolecular Diels–Alder reaction of bicyclic precursors derived from l -tyrosine. Three substituents were systematically introduced into the developed scaffolds in various combinations, demonstrating their high utility in drug discovery.